2021
DOI: 10.1111/jnc.15542
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and neurochemical effects after repeated administration of N‐ethylpentylone (ephylone) in mice

Abstract: N‐ethyl‐pentylone (NEP), also known as ‘ephylone’ and N‐ethylnorpentylone, has been identified as one of the most recent novel psychostimulants to emerge into the illicit drug market and it has been associated with some intoxications and even fatalities. However, little is known about the consequences of its repeated consumption as well as the role of the monoaminergic system in such consequences. Thus, the aim of our study was to investigate the neurochemical profile and the behavioural effects after both acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In rats, ephylone showed locomotor stimulant effects similar to methamphetamine, but was less potent than it and showed a shorter duration of action [137,138]. In addition, repeated administration of ephylone caused anxiolytic-like and depressive-like effects and aggressiveness in rats [138,139]. Studies in rodents suggest that ephylone has a high addictive potential [137,[139][140][141].…”
Section: N-ethylhexedrone Ephylone and Eutylonementioning
confidence: 99%
See 1 more Smart Citation
“…In rats, ephylone showed locomotor stimulant effects similar to methamphetamine, but was less potent than it and showed a shorter duration of action [137,138]. In addition, repeated administration of ephylone caused anxiolytic-like and depressive-like effects and aggressiveness in rats [138,139]. Studies in rodents suggest that ephylone has a high addictive potential [137,[139][140][141].…”
Section: N-ethylhexedrone Ephylone and Eutylonementioning
confidence: 99%
“…In addition, repeated administration of ephylone caused anxiolytic-like and depressive-like effects and aggressiveness in rats [138,139]. Studies in rodents suggest that ephylone has a high addictive potential [137,[139][140][141]. Additionally, studies in zebrafish showed its neurotoxicity, cardiotoxicity and developmental toxicity [142].…”
Section: N-ethylhexedrone Ephylone and Eutylonementioning
confidence: 99%